Women’s resistance to domestic violence during COVID-19 pandemic: A study from Indonesia - Siti Mas'udah; Lutfi Apreliana Megasari; Muhammad Saud (Jurnal Sosiologi Dialektika, 2021)
COVID-19 pandemic affected the increasing frequency and intensity of a husband and wife’s interaction. The pandemic further worsened domestic violence experienced by women, and this has made them resist the violence. This study aims to unravel domestic violence and women’s resistance. The research used a qualitative method on women who experienced domestic violence amid the COVID-19 pandemic. The findings suggest that the resistance was triggered by numerous internal conflicts, such as declining income and increasingly diverse household conflicts during the pandemic. Women spontaneously resist against verbal, physical, and psychological abuse to save themselves from harm and to protect their dignity. The resistances are demonstrated in various ways, including fighting the husband back, verbal abuse, shouting, threatening to divorce, scratching, and punching the husband. Additionally, women also resorted to passive resistance by giving the silent treatment, staying away, stopping communication, not sleeping in the same bed, and refusing to serve the husband. This resistance exhibited women’s awareness to defend their rights. Women did realize that they have the right to fight back as a manner of combating gender inequality.